2005
DOI: 10.1177/0013916504267639
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Feedback on Three Recycling-Related Behaviors in South Korea

Abstract: The effectiveness of posted feedback on recycling in a lounge area at a South Korean university was studied. Participants were college students, professors, and staff members. The dependent variables were the percentage and number of correctly separated aluminum cans, the percentage and number of correctly separated paper cups, and the weight of recycled paper. An A-B-BC-A time series design was used. During baseline (A), separation containers were provided. Posted written feedback was introduced (B) and graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…In order for such programs to succeed, it may be helpful to better understand the variables that influence recycling behavior. Researchers have successfully increased recycling through consequence-based interventions such as contingent rewards (e.g., Geller, Chaffee, & Ingram, 1975), public feedback (e.g., Kim, Oah, & Dickinson, 2005), and commitment (e.g., 1 Email: ndmiller@memphis.ed DeLeon & Fuqua, 1995). Two antecedent-based procedures that are particularly promising for institutional efforts to improve recycling are the placement of recycling bins in close proximity to the point of consumption (e.g., Ludwig, Gray, & Rowell, 1998;O'Connor, Lerman, Fritz, & Hodde, 2010), and providing antecedent prompts or signs (e.g., Austin, Hatfield, Grindle, & Bailey, 1993;Duffy & Verges, 2008).…”
mentioning
confidence: 99%
“…In order for such programs to succeed, it may be helpful to better understand the variables that influence recycling behavior. Researchers have successfully increased recycling through consequence-based interventions such as contingent rewards (e.g., Geller, Chaffee, & Ingram, 1975), public feedback (e.g., Kim, Oah, & Dickinson, 2005), and commitment (e.g., 1 Email: ndmiller@memphis.ed DeLeon & Fuqua, 1995). Two antecedent-based procedures that are particularly promising for institutional efforts to improve recycling are the placement of recycling bins in close proximity to the point of consumption (e.g., Ludwig, Gray, & Rowell, 1998;O'Connor, Lerman, Fritz, & Hodde, 2010), and providing antecedent prompts or signs (e.g., Austin, Hatfield, Grindle, & Bailey, 1993;Duffy & Verges, 2008).…”
mentioning
confidence: 99%
“…While most of these factors are mainly extraneous in nature, the endurance of such extrinsic factors in reinforcing recycling behaviours over a long period of time is another challenge. However, authors (such as [33,66]) have demonstrated that extrinsic motivations such as monetary rewards [42] cannot sustain recycling behaviour when compared to other factors such as feedback [77], organisation [58] and individual [45] commitment. In other words, behaviour may return to the status quo after the extrinsic incentives are withdrawn, corroborating previous studies [38] that extrinsic factors can only provide short-term effects.…”
Section: Motivating Factorsmentioning
confidence: 99%
“…on bin contamination). Indeed, [42] argued that publically posted feedback significantly increased recycling rates.…”
Section: Recycling Promotionmentioning
confidence: 99%
“…Information such as how much money is earned through recycling and what is being done with the funds could be made available through the University's various social media. A study conducted by [42] revealed that posting feedback had a positive impact on recycling rates. However, reporting the challenges associated with the Recycling Initiative are just as important as reporting the positives.…”
Section: Recycling Promotionmentioning
confidence: 99%